Randomized Phase III Trial of Temsirolimus Versus Sorafenib As Second-Line Therapy After Sunitinib in Patients With Metastatic Renal Cell Carcinoma - Hutson, Thomas E. (J Clin Oncol, 2014)
PURPOSE: This international phase III trial (Investigating Torisel As Second-Line Therapy [INTORSECT]) compared the efficacy of temsirolimus (mammalian target of rapamycin inhibitor) and sorafenib (vascular endothelial growth factor receptor [VEGFR] tyrosine kinase inhibitor) as second-line therapy in patients with metastatic renal cell carcinoma (mRCC) after disease progression on sunitinib. PATIENTS AND METHODS: In total, 512 patients were randomly assigned 1:1 to receive intravenous temsirolimus 25 mg once weekly (n = 259) or oral sorafenib 400 mg twice per day (n = 253), with stratification according to duration of prior sunitinib therapy (≤ or > 180 days), prognostic risk, histology (clear cell or non–clear cell), and nephrectomy status. The primary end point was progression-free survival (PFS) by independent review committee assessment. Safety, objective response rate (ORR), and overall survival (OS) were secondary end points. RESULTS: Primary analysis revealed no significant difference between treatment arms for PFS (stratified hazard ratio [HR], 0.87; 95% CI, 0.71 to 1.07; two-sided P = .19) or ORR. Median PFS in the temsirolimus and sorafenib arms were 4.3 and 3.9 months, respectively. There was a significant OS difference in favor of sorafenib (stratified HR, 1.31; 95% CI, 1.05 to 1.63; two-sided P = .01). Median OS in the temsirolimus and sorafenib arms was 12.3 and 16.6 months, respectively. Safety profiles of both agents were consistent with previous studies. CONCLUSION: In patients with mRCC and progression on sunitinib, second-line temsirolimus did not demonstrate a PFS advantage compared with sorafenib. The longer OS observed with sorafenib suggests sequenced VEGFR inhibition may benefit patients with mRCC.